Evaluating the effects of bedding materials and elevated platforms on contact dermatitis and plumage cleanliness of commercial broilers and on litter condition in broiler houses. Issue 5 (3rd September 2017) - Kaukonen, E.; Norring, M.; Valros, A.
ABSTRACT: 1. Experiment 1, comparing wood shavings and ground straw bedding with peat, was performed on 7 broiler farms over two consecutive batches during the winter season. Experiment 2, assessing the effect of elevated (30 cm) platforms, was conducted in three farms replicated with 6 consecutive batches. 2. Footpad lesions were inspected at slaughter following the Welfare Quality® (WQ) assessment and official programme. Hock lesions, plumage cleanliness and litter condition were assessed using the WQ assessment. Litter height, pH, moisture and ammonia were determined. 3. Footpad condition on wood shavings appeared to be worse compared with peat using both methods of assessment and was accompanied by inferior hock skin health. WQ assessment resulted in poorer footpad and hock skin condition on ground straw compared with peat. Farms differed in footpad and hock skin condition. Footpad and hock lesions were not affected by platform treatment. Peat appeared more friable than ground straw. The initial pH of wood shavings was higher and moisture was lower than in peat, but at the end of production period there were no differences. Ground straw exhibited higher initial and lower end pH, and was drier in the beginning than peat. Litter condition and quality were not affected by platform treatment. 4. This study provides new knowledge about the applicability of peat as broiler bedding and shows no negative effects of elevated platforms on litter condition or the occurrence of contact dermatitis in commercial environments. The results suggest a complicated relationship between litter condition, moisture and contact dermatitis. Furthermore, it is concluded that the farmer's ability to manage litter conditions is important, regardless of the chosen litter material. Peat bedding was beneficial for footpad and hock skin health compared with wood shavings and ground straw.